2014
DOI: 10.1016/s1473-3099(13)70304-9
|View full text |Cite
|
Sign up to set email alerts
|

Middle East respiratory syndrome coronavirus: quantification of the extent of the epidemic, surveillance biases, and transmissibility

Abstract: SummaryBackgroundThe novel Middle East respiratory syndrome coronavirus (MERS-CoV) had, as of Aug 8, 2013, caused 111 virologically confirmed or probable human cases of infection worldwide. We analysed epidemiological and genetic data to assess the extent of human infection, the performance of case detection, and the transmission potential of MERS-CoV with and without control measures.MethodsWe assembled a comprehensive database of all confirmed and probable cases from public sources and estimated the incubati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
374
6
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(408 citation statements)
references
References 18 publications
20
374
6
8
Order By: Relevance
“…The risk of involving tertiary, quaternary and quinary cases was also calculated ( Figure 2B). Although our study only relied upon importation events consisting of a small number of clusters, the estimated R 0 was broadly consistent with published estimates that analysed larger cluster datasets mainly observed in Middle East countries [3][4][5] and was smaller than estimates derived from the early phase of hospitalassociated outbreaks [13]. Considering that countries at risk of importation (i.e.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The risk of involving tertiary, quaternary and quinary cases was also calculated ( Figure 2B). Although our study only relied upon importation events consisting of a small number of clusters, the estimated R 0 was broadly consistent with published estimates that analysed larger cluster datasets mainly observed in Middle East countries [3][4][5] and was smaller than estimates derived from the early phase of hospitalassociated outbreaks [13]. Considering that countries at risk of importation (i.e.…”
Section: Discussionsupporting
confidence: 87%
“…Firstly, our exercise regarded each observed importation event as a random draw governed by the proposed probability model. Indeed, this assumption is unavoidable for fitting a branching process model to the data [3,4]. While the assumption may be common among modelling studies, it did not allow us to account for the variable type and effectiveness of interventions, especially at later generations of cases in each cluster.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Gierer et al, did not detect MERS-CoV neutralizing antibodies in any of the 268 samples tested that were obtained from persons from the Eastern province of Saudi Arabia 74 . Using independent data sources, different investigators demonstrated that R, the basic reproduction number representing the number of secondary cases per index case in a fully susceptible population, cannot be much above 1, with an upper bound of 1.2 -1.5 69,75 .…”
Section: Mers-cov Infection In Animals Appearsmentioning
confidence: 99%
“…The MERS has also been transmitted to other countries through travelers infected in Arabian Peninsula and neighboring countries. Human-to-human transmission has been observed to a limited extent in households and healthcare workers (Cauchemez et al, 2014).…”
Section: Transmissionmentioning
confidence: 99%